2008
DOI: 10.1111/j.1469-0691.2008.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of methicillin-resistant Staphylococcus epidermidis strains from bacteraemic patients

Abstract: In order to study the clonality of clinical methicillin-resistant Staphylococcus epidermidis (MRSE) strains and their staphylococcal cassette chromosome mec (SCCmec) elements, 60 isolates of MRSE from bacteraemic patients in three units of the Helsinki University Hospital, Finland were selected, covering the periods 1990-1993 and 1997-1998. The MRSE strains were analysed by pulsed-field gel electrophoresis (PFGE), multilocus sequence typing and SCCmec typing. Eleven PFGE types (FIN-SE-1-11) with sequence type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
7
25
0
Order By: Relevance
“…Several investigations have demonstrated that certain multidrug-resistant S. epidermidis (MDRSE) genotypes become established as opportunistic pathogens in the health care setting as a novel ecological niche (8,10,12). In addition, recent studies identified several worldwide epidemic clonal lineages (9,12,13,18,21).…”
mentioning
confidence: 99%
“…Several investigations have demonstrated that certain multidrug-resistant S. epidermidis (MDRSE) genotypes become established as opportunistic pathogens in the health care setting as a novel ecological niche (8,10,12). In addition, recent studies identified several worldwide epidemic clonal lineages (9,12,13,18,21).…”
mentioning
confidence: 99%
“…Up to now, six different SCCmec types (I to VI) have been recognized, each of which is different in size (21 to 67 kb) and characterized by a different set of ccr recombinase genes and mec gene complex (3,12,13,22,24,32). In addition to the major types, a number of new SCCmec elements, including non-mecA-encoding cassettes, have been discovered (2,3,11,16,19,20,28). New types may be generated continuously (5,9).…”
mentioning
confidence: 99%
“…Resistance to fluoroquinolones, erythromycin, clindamycin, gentamicin, rifampin, tetracycline, and chloramphenicol is also frequent (1,(6)(7)(8). Multilocus sequence typing (MLST) analysis suggests that multidrug resistance in S. epidermidis is associated with a small number of related clones, mostly belonging to ST2 and related sequence types (STs) (9)(10)(11).…”
mentioning
confidence: 99%